"Shirobako":The Representation of Passion and Creative Labor in Japanese Animation Industry - Upik Sarjiati (Jurnal Kawistara, 2021)
Common narratives of the industry include extensive working hours, minimal wages and uncertain conditions. However, there are many creative workers desire to work in anime industry mainly due to passion. The purpose of this research is to analyze the representation of passion and creative labor in Japanese animation industry. Shirobako series provides a case study describing an animated movie production process. Studies on visual and narrative of anime have been conducted; however the study on the production aspect is limited. This study aims to portray anime production complexities and creative labor dynamic. Using constructive approach by Stuart Hall, this study assesses passion on individual and collaborative levels. Based on the results, the passion of creative personnel was personally and subjectively defined. This drive triggers the capacity to acquire new knowledge and endure challenging situations. Furthermore, information sharing and commitment are important qualities of collaborative production. In general, the Shirobako series acknowledged a power relationship gap between production committee members and the creative workforce.